Creative Economy in Brazil: A study of legal frameworks, subnational actions and proposal for institutionalization (Management and Connections Journal, 2025)
This study analyzes the process of institutionalization of the creative economy in Brazil, focusing on the legal frameworks and public policies adopted at the federal and subnational levels. Applied in nature, qualitative and with a descriptive exploratory approach, the research was structured in three stages: (1) survey and analysis of the federal legal framework, through the portals of the Federal Senate and the Chamber of Deputies, considering the theme of the creative economy; (2) mapping of actions and guidelines in the 26 Brazilian states and the Federal District, using the term “creative economy” as a search criterion; and (3) systematic literature review as theoretical support. The results reveal the need for a national regulatory framework, in view of the weak institutionalization of policies for the creative economy, normative discontinuity and low articulation among federative entities, especially at the state level. As a response to this scenario, a framework is proposed, based on specialized literature and contemporary legislation, composed of nine structuring actions. The focus of the actions was to provide subsidies for strengthening discussions on the creative economy and for the creation of a national and local governance articulated in public policies aimed at the creative economy.
Keywords: public policies; creativity; regional development; public management; cultural economy